Gancidin W, a potential low-toxicity antimalarial agent isolated from an endophytic Streptomyces SUK10 - Zin NM; Baba MS; Zainal-Abidin AH; Latip J; Mazlan NW; Edrada-Ebel R (Dove Medical Press, 2017)
Noraziah Mohamad Zin,1 Mohd Shukri Baba,2 Abu Hassan Zainal-Abidin,3 Jalifah Latip,4 Noor Wini Mazlan,5 RuAngelie Edrada-Ebel6 1Programme of Biomedical Science, School of Diagnostic and Applied Health Sciences, Faculty of Health Sciences, Universiti Kebangsaan Malaysia, Kuala Lumpur, 2Department of Biomedical Sciences, Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, Kuantan, 3Department of Parasitology, Faculty of Medicine, Universiti Teknologi MARA, Shah Alam, 4School of Chemical Sciences and Food Technology, Faculty of Science and Technology, Universiti Kebangsaan Malaysia, Bangi, 5Analytical and Environmental Chemistry, School of Marine and Environmental Sciences, Universiti Malaysia Terengganu, Kuala Terengganu, Malaysia; 6Strathclyde Institute of Pharmacy and Biomedical Sciences, University of Strathclyde, Glasgow, UK Abstract: Endophytic Streptomyces strains are potential sources for novel bioactive molecules. In this study, the diketopiperazine gancidin W (GW) was isolated from the endophytic actinobacterial genus Streptomyces, SUK10, obtained from the bark of Shorea ovalis tree, and it was tested in vivo against Plasmodium berghei PZZ1/100. GW exhibited an inhibition rate of nearly 80% at 6.25 and 3.125 µg kg-1 body weight on day four using the 4-day suppression test method on male ICR strain mice. Comparing GW at both concentrations with quinine hydrochloride and normal saline as positive and negative controls, respectively, 50% of the mice treated with 3.125 µg kg-1 body weight managed to survive for more than 11 months after infection, which almost reached the life span of normal mice. Biochemical tests of selected enzymes and proteins in blood samples of mice treated with GW were also within normal levels; in addition, no abnormalities or injuries were found on internal vital organs. These findings indicated that this isolated bioactive compound from Streptomyces SUK10 exhibits very low toxicity and is a good candidate for potential use as an antimalarial agent in an animal model. Keywords: antimalarial, Shorea ovalis, in vivo, endophytic, Streptomyces, gancidin W